An assessment of family medicine residents’ and early career physicians’ perceptions of their training: A survey from a single Canadian university - Todd, Keith J; Fournier, Sandra; Sandhu, Amrita; Zahedi, Sima; Hersson-Edery, Fanny; Dove, Marion (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Background: To determine if family medicine residents and recent graduates believe that the current residency program is sufficiently meeting their training needs for independent practice.Methods: In 2024, a brief online survey using Likert scale and open-text questions evaluated McGill University residents’ and graduates’ level of agreement that family medicine residency training allows them to develop the necessary clinical knowledge and skills across nine domains. Medians and interquartile ranges were calculated to understand agreement and consensus of responses. Latent content analysis was conducted on qualitative responses. Results: Across 10 sites, 31 of 158 senior residents responded and 59 of 452 residency graduates participated. With high levels of agreement and consensus, participants reported their learning needs were being met in most domains of care. However, graduate responses suggest that the program did not meet their learning needs for Indigenous health and procedural skills. Additionally, resident responses had low consensus around care of vulnerable and marginalized populations.Conclusions: Learner needs may not be met in three domains of care within the family medicine residency program, a finding that aligns with the recent call for curricular reform in Canada. These results could help focus curriculum reform priorities to areas of greatest need.